ANALISIS PENGUKURAN KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO CAMEL (Study Kasus PT. Bank Bengkulu) - Hernadianto Hernadianto; Ofti Horina; Nour Ardiansyah (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACTThe world of banking in Indonesia enters a period of very competitive competition, this is due to the large number of banks operating in Indonesia. The rapid development of the banking world and the high level of complexity of banking businesses can affect the financial performance of a bank. The formulation of the problem in this study is how the performance of PT. Bank Mandiri (Persero) Tbk which is measured by the provisions of Bank Indonesia concerning the assessment of the soundness of banks by using CAMEL financial ratio. This research is a quantitative descriptive study which aims to analyze the health level of PT. Bank Mandiri (Persero) Tbk for the period 2015-2017 using the CAMEL method which includes capital (capital), asset quality (asset quality), management (management), earnings (earnings), and liquidity (likuidity). Based on the results of the analysis of the Bank's health level using the CAMEL ratio for the period 2015-2017 overall it can be said that in general the performance and health of PT. Bank Mandiri (Persero) Tbk in a healthy condition. Â Keywords: Bank financial performance, CAMEL (capital, asset quality, management, aeming, liquidity)Â